Molecular characterization of heat shock protein 20 (hsp20) in goldfish (Carassius auratus) and expression analysis in response to environmental stresses - Wenbo Chen; Mengna Zhang; Xurui Luo; Zhen Zhang; Xuesong Hu (Aquaculture Reports, 2022)
Heat shock proteins (Hsps) are described as molecular chaperones that were synthesized rapidly in response to various stress conditions in many organisms. However, information of small heat shock protein (sHsp) in response to environmental stresses is lacking in fish. In this study, the full length cDNA of hsp20 in goldfish, Carassius auratus, with a 65 bp 5′-untranslated region (UTR), a 563 bp 3′-UTR, and a 450 bp open reading frame encoding 149 amino acids, was obtained. gfhsp20 contained a highly conserved α-crystallin domain. Consistent with humans and zebrafish, goldfish HSP20 gene had three exons and two introns. gfhsp20 mRNA were detected by quantitative real-time PCR in all of the tissues examined, with the highest level in the muscle, followed by the skin, heart, intestine, liver, spleen, brain, kidney, gill and head kidney. gfhsp20 mRNA was significantly induced with heat shock in liver and spleen, but decreased in brain. Under H2O2-mediated oxidative stress, the expression level of gfhsp20 was significantly up-regulated in brain, liver and spleen. After LPS and PolyI:C infection, the expression level of gfhsp20 in spleen was significantly up-regulated with a higher increase under PolyI:C infection than that of LPS injection. These results revealed the potential function of gfHsp20 in response to heat shock, oxidative stress and infectious pathogens.